Peristalsis in the junction region of the Drosophila larval midgut is modulated by DH31 expressing enteroendocrine cells. - Lajeunesse, D.R.; Johnson, B.; Presnell, J.S.; Catignas, K.K.; Zapotoczny, G. (BMC physiology, 2010)
The underlying cellular and molecular mechanisms that coordinate the physiological processes in digestion are complex, cryptic, and involve the integration of multiple cellular and organ systems. In all intestines, peristaltic action of the gut moves food through the various stages of digestion from the anterior end towards the posterior, with the rate of flow dependent on signals, both intrinsic and extrinsic to the gut itself.We have identified an enteroendocrine cell type that regulates gut motility in the Drosophila melanogaster larval midgut. These cells are located at the junction of the anterior and the acidic portions of the midgut and are a group of enteroendocrine cells that express the peptide hormone Diuretic Hormone 31 in this region of the gut. Using cell ablation and ectopic activation via expression of the Chlamydomonas reinhardtii blue light-activated channelopsin, we demonstrate that these enteroendocrine cells are both necessary and sufficient for the peristalsis in the junction region of the midgut and require the Diuretic Hormone 31 to affect normal peristalsis in this region. Within the same junction region of the midgut, we have also identified morphological features suggesting that this region acts as a valve that regulates the transit of food from the anterior midgut into the acidic portion of the gut.We have characterized and described a set of enteroendocrine cells called the Midgut Junction DH31 expressing cells that are required for peristaltic movement in the junction region between the anterior portion and acidic region of the larval midgut of Drosophila melanogaster. We have shown that the Midgut Junction DH31 expressing cells are necessary and sufficient for motility and that the peptide hormone DH31 is required for peristalsis in the junction region of the midgut. The Drosophila model system will allow for a further dissection of the digestion process and provide a better understanding of the mechanisms that regulate digestion in all organisms.